Genetic analysis of the guanylate cyclase activator 1B (GUCA1B) gene in patients with autosomal dominant retinal dystrophies. Issue 9 (1st September 1999) - Payne, Annette M; Downes, Susan M; Bessant, David A R; Plant, Catherine; Moore, Tony; Bird, Alan C; Bhattacharya, Shomi S
Abstract : The guanylate cyclase activator proteins (GCAP1 and GCAP2) are calcium binding proteins which by activating Ret-GC1 play a key role in the recovery phase of phototransduction. Recently a mutation in the GUCA1A gene (coding for GCAP1) mapping to the 6p21.1 region was described as causing cone dystrophy in a British family. In addition mutations in Ret-GC1 have been shown to cause Leber congenital amaurosis and cone-rod dystrophy. To determine whether GCAP2 is involved in dominant retinal degenerative diseases, the GCAP2 gene was screened in 400 unrelated subjects with autosomal dominant central and peripheral retinal dystrophies. A number of changes involving the intronic as well as the coding sequence were observed. In exon 1 a T to C nucleotide change was observed leaving the tyrosine residue 57 unchanged. In exon 3 a 1 bp intronic insertion, a single nucleotide substitution G to A in the intron 3′ of this exon, and a GAG to GAT change at codon 155 were observed. This latter change results in a conservative change of glutamic acid to aspartic acid. In exon 4 a 7 bp intronic insertion, a single nucleotide A to G substitution in the intron 5′ of this exon, and a single base pair change C to G in the intron 3′ of exon 4 were seen. None of these changes would be expected to affect correct splicing of this gene. All these changes were observed in controls. The results of this study do not show any evidence so far that GCAP2 is involved in the pathogenesis of autosomal dominant retinal degeneration in this group of patients. All the changes detected were found to be sequence variations or polymorphisms and not disease causing.